AI recognition for User's Emotion from Facial Images Using Neural Network - Gangwar, Manjari (JOURNAL OF BUSINESS MANAGEMENT & QUALITY ASSURANCE, 2022)
The method employs many of the temporal information displayed in the video analysis. The emphasis behind using all of the temporal information is that any emotion being displayed has a unique temporal pattern. Many of the facial expression research works classified each frame of the video to a facial expression based on some set of features computed for that time frame. Keywords: facial expression, features, emphasis, temporal information.